Animal Disease and Human Trauma - Convery, I. author. aut Link
XVII, 184 p.
Keywords: Many disasters are approached by researchers, managers and policymakers as if they have a clear beginning, middle and end. But often the experience of being in a disaster is not like this. This book offers non-linear, non-prescriptive ways of thinking about disasters and allows the people affected by disaster the chance to speak.